2018
DOI: 10.1002/jgf2.199
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pneumonia care quality between general physicians and pulmonologists

Abstract: BackgroundWe compared the quality of care for nursing‐ and healthcare‐associated pneumonia (NHCAP) and aspiration pneumonia provided by general physicians and pulmonologists.MethodsQuestionnaires were mailed to 2490 medical facilities across Japan. The questionnaire assessed participants’ implementation of microbiological investigations for NHCAP or aspiration pneumonia, as well as steps taken to prevent pneumonia recurrence (eg, use or discontinuation of drugs associated with swallowing and administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Our findings suggest that the care provided to non-COVID-19 CAP patients admitted under GM units was more efficient compared to those admitted under Respiratory units. Consistent with previous studies [2,8] our results indicate that there was no compromise in the quality of care for GM patients, as evidenced by comparable in-hospital mortality and 30-day readmission rates between the two units. Prior research has demonstrated that a shorter LOS for CAP patients is associated with reduced healthcare costs [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings suggest that the care provided to non-COVID-19 CAP patients admitted under GM units was more efficient compared to those admitted under Respiratory units. Consistent with previous studies [2,8] our results indicate that there was no compromise in the quality of care for GM patients, as evidenced by comparable in-hospital mortality and 30-day readmission rates between the two units. Prior research has demonstrated that a shorter LOS for CAP patients is associated with reduced healthcare costs [24].…”
Section: Discussionsupporting
confidence: 92%
“…Limited evidence exists regarding the characteristics and outcomes of CAP patients admitted under generalist versus respiratory care. Some studies have suggested comparable outcomes [2,8], while others [9] have indicated potential benefits, such as reduced mortality and shorter LOS, associated with admission to Respiratory units. These benefits may stem from expedited antibiotic initiation, use of adjunctive therapies such as corticosteroids and early use of fibre optic bronchoscopy which can aid in early pathogen detection [9].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that the care provided to non-COVID-19 CAP patients admitted under GM units was more efficient compared to those admitted under Respiratory units. Consistent with previous studies [6,12], our results indicate that there was no compromise in the quality of care for GM patients, as evidenced by comparable in-hospital mortality and 30-day readmission rates between the two units. Prior research has demonstrated that a shorter LOS for CAP patients is associated with reduced healthcare costs [27].…”
Section: Discussionsupporting
confidence: 91%
“…Limited evidence exists regarding the characteristics and outcomes of CAP patients admitted under generalist versus respiratory care. Some studies have suggested comparable outcomes [6,12], while others [13] have indicated potential benefits, such as reduced mortality and shorter LOS, associated with admission to Respiratory units. These benefits may stem from expedited antibiotic initiation, the use of adjunctive therapies such as corticosteroids, and the early use of fibre optic bronchoscopy which can aid in early pathogen detection [13].…”
Section: Introductionmentioning
confidence: 99%